P225 Personal perception and impact of work aggravated asthma. (15th November 2017) - Bradshaw, LM; Sumner, J; Delic, J; Fishwick, D
Abstract : Workers with asthma frequently complain asthma symptoms are worse at work. Work aggravated asthma (WAA) is asthma made worse by but not caused by workplace exposures. Work practices and exposures can affect asthmatics with mild, moderate or severe asthma. The aim of this study was to explore the personal perception and impact of WAA. A purposive sampling strategy was used to recruit subjects into this study. The sample was selected from a group of participants in a WAA cross sectional postal questionnaire study. For enrichment qualitative data was also used from the postal questionnaire. All subjects had self-reported WAA and were stratified according to asthma severity. Data were analysed using thematic analysis. Eighty five subjects provided qualitative data from the postal questionnaire, 6 subjects were interviewed with an in depth face to face interview and one subject an in depth telephone interview. No further interviews were conducted when data saturation point was met. Five main themes concerning the workers perception of WAA were identified. These were; the working environment, lack of understanding about asthma, mental health, social impact and financial impact. Workers believed that a variety of triggers within the workplace caused them to have asthma symptoms. High levels of stress impacted on quality of life and job satisfaction. Some workers were willing to leave the workplace or change career because of the emotional impact feeling stressed at work had on their lives. WAA had an impact on social and family life with individuals giving up socialising when they had asthma symptoms. Feelings of guilt for relying on a partner, children and family to care for them were common. The financial burden of buying inhalers, attending appointments and in some cases reducing working hours or changing to less well paid roles had an impact. There was a perception that employers and colleagues had a lack of understanding of asthma, in particular the variable nature of the disease. Asthma education programmes in workplaces could help employers and workers understand how to deal with a colleague with asthma and alleviate the stress those workers with WAA experience.